Pengembangan E-LKPD IPAS berbasis Keterampilan Proses Sains pada Materi Gaya dan Gerak - Nadia Alfiani Fitriah; Sandi Budiana; Fitri Siti Sundari (STKIP Subang, 2023)
This study aims to determine the development of E-LKPD IPAS based on Science Process Skills in the Material of Style and Motion in class IV at SDN Pabuaran Cilendek Bogor City and to determine the feasibility of E-LKPD IPAS based on Science Process Skills for the learning process. The method used in this research is using the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). This research begins with a needs analysis, designing the E-LKPD, validating it by experts, revising the E-LKPD, after that it is doing a limited E-LKPD trial and evaluation. The results showed that E-LKPD IPAS based on Science Process Skills had met the very feasible criteria by obtaining a percentage of 100% from media experts, 100% from linguists and 94% from material experts. Meanwhile, the limited trial conducted on 23 grade IV students obtained a response with a percentage of 93% and a teacher response with a percentage of 98%. Based on these data, it can be concluded that the E-LKPD is very feasible to be used by students and teachers as teaching materials on force and motion in grade IV of elementary school.